Der Kategorienkommentar von Abū l-Farağ ʿAbdallāh ibn aṭ-Ṭayyib : Text und Untersuchungen - Ferrari, Cleophea, (Aristoteles Semitico-Latinus ;, 2006)
The Commentary on the Categorie s by Abū l-Farağ ibn aṭ-Ṭayyib is an important representative of the Aristotelian tradition in Arabic culture. Formally based on late antique commentaries on Aristotle's Categories , it provides the last example of the learned tradition still alive in eleventh-century Baghdad. The introduction offers a general survey of the commentaries on Aristotelian Categories , from the first Greek texts to the Arabic version featured here. The life and works of Ibn aṭ-Ṭayyib are also discussed. Systematic comparison with surviving Greek commentaries and a series of thematic studies elucidate the author´s method. The critical edition of ibn aṭ-Ṭayyib's Commentary is accompanied by a detailed summary, which facilitates its use by readers unfamiliar with the Arabic language.